2019
DOI: 10.3389/fimmu.2019.02486
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 Post-translational Modifications and Treg Suppressive Activity

Abstract: Regulatory T cells (Tregs) are engaged in maintaining immune homeostasis and preventing autoimmunity. Treg cells include thymic Treg cells and peripheral Treg cells, both of which can suppress the immune response via multiple distinct mechanisms. The differentiation, proliferation, suppressive function and survival of Treg cells are affected by distinct energy metabolic programs. Tissue-resident Treg cells hold unique features in comparison with the lymphoid organ Treg cells. Foxp3 transcription factor is a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 167 publications
(171 reference statements)
1
82
0
Order By: Relevance
“…Treg cells are essential for maintaining peripheral immune tolerance, preventing autoimmune diseases and limiting chronic inflammatory diseases by secreting IL-10 [30,31]. Some studies have reported that the function of Treg cells in RA is partially impaired or that Treg cell number is decreased [32].…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells are essential for maintaining peripheral immune tolerance, preventing autoimmune diseases and limiting chronic inflammatory diseases by secreting IL-10 [30,31]. Some studies have reported that the function of Treg cells in RA is partially impaired or that Treg cell number is decreased [32].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report that the development and function of Treg cells can be regulated by the acetylation status of FOXP3. In addition, hyperacetylation of FOXP3 can prevent the polyubiquitination and proteasomal degradation of FOXP3, leading to an improved stability and transcriptional activity of FOXP3 and GvHD suppression [108][109][110][111][112][113].…”
Section: Effect Of Hdac Inhibitors On Donor T Cell Activation and Difmentioning
confidence: 99%
“…Additionally, similar to most transcription factors, FoxP3's function can be modulated by post-translational modifications (such as ubiquitination, acetylation, and phosphorylation), which couple extracellular cues to adjustments of transcriptional programmes [for a review see (22,23)].…”
Section: Treg Cells In Health the Foxp3 Transcription Factormentioning
confidence: 99%